Analisis Aspek Kompetensi Individu dalam Duplikasi Nomor Rekam Medis di Puskesmas - Ida Nurmawati; Kurnia Arofah (Politeknik Negeri Jember, 2019)
Duplication of medical record number is one of the problems in medical record section. Duplication that occurred in the Labruk Kidul Public Health Center was 10,3% consist of 7,6% duplicate one medical record number owned by some head of families, and 2,7% duplicated one head of family with some medical record numbers. The purpose of this research is to analyze the priority causes of duplication medical record of numbers in the Labruk Kidul Public Health Center Lumajang. It was a qualitative research and the data collection techniques used interviews,and observations. The subject of this research was registration officer, head of the medical record and head of the public health center. The results showed that the cause of duplication from individual competency factors was that the officer could not make KIUP, the officer did not write the. The solution is to socialize the system of numbering and additional time and labor in finding duplicate medical record number and merging files.